1988
DOI: 10.1139/b88-058
|View full text |Cite
|
Sign up to set email alerts
|

The chemotaxonomic significance of laricytrin and medicagenic acid in the tribe Trigonelleae

Abstract: JURZYSTA, M., BURDA, S., OLESZEE, W., and PLOSZYNSKI, M. 1988. The chemotaxonormic significance of laricytrin and medicagenic acid in the tribe Trigonelleae. Can. J. Bot. 66: 363 -367. Flavonoids Prom fresh flowers of 35 species and medicagenic acid from leaf tissue of 44 species of the tribe Trigonelleae Schulz (Fabaceae) were examined using thin-layer chromatography. Moreover, medicagenic acid glycosides in the leaf tissue were dso analyzed by the hemolytic test. Compounds tentatively identified as kaempfeml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Moreover, their presence was also confirmed in M. lupulina roots (Oleszek et al, 1988a). It has been shown that while M. media contained in its roots at least 11 medicagenic acid glycosides (Oleszek and Jurzysta, 1986a), the 3-0-mono-and 3,28-di-( O-glucopyranoside) of medicagenic acid were the only compounds of this kind in M. lupulina roots.…”
Section: Chemical Characteristics Of Alfalfa Sap On Insmentioning
confidence: 79%
“…Moreover, their presence was also confirmed in M. lupulina roots (Oleszek et al, 1988a). It has been shown that while M. media contained in its roots at least 11 medicagenic acid glycosides (Oleszek and Jurzysta, 1986a), the 3-0-mono-and 3,28-di-( O-glucopyranoside) of medicagenic acid were the only compounds of this kind in M. lupulina roots.…”
Section: Chemical Characteristics Of Alfalfa Sap On Insmentioning
confidence: 79%
“…Their content in the plant material changes as a function of several factors, such as plant organs, genotype, cutting, year and stage of growth, and environmental effects, as reported for M. sativa, the most studied species of the genus [50][51][52][53][54][55]. The chemotaxonomic significance of saponins has also been investigated as their composition can discriminate among Medicago species [56][57][58][59]. The occurrence of saponins in the Medicago genus is long known [60], and their composition has been studied in several species.…”
mentioning
confidence: 99%
“…Finally, 73 was unequivocally assigned by comparison with a silylated reference standard ( 73 ‐TMS). Even though the occurrence of 73 has been previously reported as saponin constituent from other members of the Fabaceae family, it has not been found in A. vulneraria before [41–44] . Thus, an interesting task of future investigations may be the isolation and structure elucidation of medicagenic acid glycosides (saponins) from the polar fraction of A. vulneraria .…”
Section: Resultsmentioning
confidence: 96%